Identity dilemma of light-skinned Black protagonist in England in Never Far from Nowhere by Black British writer Andrea Levy - Wang, Juan; Singh, Hardev Kaur Jujar; Toh Haw Ching, Florence (Universiti Putra Malaysia, 2026)
Light-skinned Black citizens are often perceived as integrating into predominantly white societies more easily than their dark-skinned counterparts. However, the identity dilemma encountered by Vivien, the light-skinned Black protagonist in Never Far from Nowhere (1996) by Andrea Levy, challenges this assumption. Vivien’s adolescent experiences reveal that her identity struggles are more complex than those of her dark-skinned sister, Olive. While past studies of the novel primarily examine Black characters’ social mobility and their varying attitudes toward Black identity, there remains a gap in scholarship regarding how differing social perceptions of the light-skinned protagonist Vivien influence her sense of belonging in England. This study focusses on Vivien’s pre-encounter stage in her understanding of Black identity, emphasising how multiple external pressures contribute to the fragmentation of her identity. Frantz Fanon’s concept of the “epidermalisation of inferiority” is employed to analyse how the ideology of Black inferiority, rooted in the colonial era, shapes Vivien’s negative attitude toward Black identity in postcolonial England. Additionally, Tajfel and Turner’s concept of social categorisation is used to investigate how these external pressures affect Vivien’s sense of belonging. This study aims to enrich existing research on the double marginalisation experienced by light-skinned Black individuals within predominantly white societies, marginalisation that comes both from white society and from the Black community. The findings suggest that significant divergence exists in how Black citizens’ racial identity is perceived both within white society and among Black individuals themselves, further intensifying Vivien’s identity dilemma.